2023
DOI: 10.1097/md.0000000000035088
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of statins in the treatment of rheumatoid arthritis: A systematic review and meta-analysis

Conglin Ren,
Mingshuang Li

Abstract: Background: A large body of research has investigated the use of statins in rheumatoid arthritis (RA); however, the therapeutic effects of statins remain uncertain. Thus, we designed a systematic review and meta-analysis to evaluate the role of statins in patients with RA. Methods: Databases searched to detect clinical randomized controlled trials or clinical controlled trials on the interaction between statins and RA before January 2020 included PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…It has been revealed that treatment with simvastatin could reduce several serum inflammatory markers in RA patients [ 52 ]. This finding was also observed in a recent meta-analysis, where Ren et al showed that the use of statins can reduce inflammatory markers of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), as well as alleviate the disease activity and symptoms of RA patients [ 53 ]. Taken together, considering the anti-inflammatory and lipid-lowering properties, statins might be used as a supplement to existing RA treatment regimens, and provide additional benefits in controlling disease activity and improving patient outcomes.…”
Section: Discussionsupporting
confidence: 55%
“…It has been revealed that treatment with simvastatin could reduce several serum inflammatory markers in RA patients [ 52 ]. This finding was also observed in a recent meta-analysis, where Ren et al showed that the use of statins can reduce inflammatory markers of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), as well as alleviate the disease activity and symptoms of RA patients [ 53 ]. Taken together, considering the anti-inflammatory and lipid-lowering properties, statins might be used as a supplement to existing RA treatment regimens, and provide additional benefits in controlling disease activity and improving patient outcomes.…”
Section: Discussionsupporting
confidence: 55%
“…The ability of statins to reduce CD4 + CD28 null T-cell levels and dampen pathological inflammatory responses suggests that these drugs may have utility in other inflammatory contexts, including age-related disorders. Indeed, statin use has been a proposed therapeutic avenue for many pathologies with some encouraging results in animal models and human randomized controlled trials ( 15 , 16 ). When assessing statin efficacy, meaningful improvements may be overlooked when pooling all patients together as not all in the sample may have comparable levels of CD4 + CD28 null T-cell expansion.…”
Section: Research Lettermentioning
confidence: 99%